Biochemical responses and accumulation patterns of Mytilus galloprovincialis exposed to thermal stress and Arsenic contamination - Coppola, Francesca (2020)
Organisms in marine systems are exposed to multiple stressors that create a range of associated environmental and ecotoxicological risks. Examples of stressors include alterations related to climate change, such as temperature increase, and the exposure to pollutants arising from human activities. The present study evaluated the impacts of Arsenic exposure (1 mg/L) and warming (21 °C) in Mytilus galloprovincialis, acting alone and in combination. Our results demonstrated that both Arsenic exposure and warming induced oxidative stress and reduced mussels metabolism, with changes becoming more prominent with the exposure time and when mussels were exposed to both stressors in combination. Furthermore, results obtained showed higher As accumulation in organisms exposed to warming treatments. The present study showed that under warming scenarios, the negative impacts induced by As may be enhanced in ecologically and economically relevant bivalves, with potential impacts on population stocks due to increased sensitivity to pollutants, which may eventually result in biodiversity loss and socio-economic impacts.